2017
DOI: 10.1039/c7ra07590a
|View full text |Cite
|
Sign up to set email alerts
|

The selective response of a templated polymer for the cationic drug pentamidine: implications from molecular simulations and experimental data

Abstract: In this paper, we present an analysis of the surface modifications responsible for the selectivity of a new imprinted sorbent produced for the isolation of pentamidine cations. We examined the polymers formed from acrylic acid as the monomer, ethylene glycol dimethacrylate as the cross-linker and 4-methoxybenzamidine as the template. A molecular simulation showed the creation of the complex surface system joined with the protonation of the template molecule in a prepolymerization complex.Polymer cavity models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Attempts of using the MD method to model binding [195][196][197][198][199][200][201][202][203][204][205][206][207] and/or structural aspects [208][209][210] of the resulting polymer have been reported. In a study by Mizaikoff and co-workers [195], hollow tubes were created by sequential stacking of rings of functional monomers, Figure 5b.…”
Section: Simulations Of Mip Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts of using the MD method to model binding [195][196][197][198][199][200][201][202][203][204][205][206][207] and/or structural aspects [208][209][210] of the resulting polymer have been reported. In a study by Mizaikoff and co-workers [195], hollow tubes were created by sequential stacking of rings of functional monomers, Figure 5b.…”
Section: Simulations Of Mip Structure and Functionmentioning
confidence: 99%
“…With the aim of identifying factors underlying MIP affinity and selectivity, Sobiech and coworkers [198][199][200]203] employed a MD-based strategy to mimic binding site models. The method involved MD simulation of pre-arranged complexes between template, functional monomer and crosslinker whereafter the template was removed, and the polymerizing step mimicked by creation of new bonds between the vinyl groups of monomers and crosslinkers.…”
Section: Simulations Of Mip Structure and Functionmentioning
confidence: 99%
“…Stationary binding experiments were performed to evaluate the binding abilities of the MIPs and the NIPs in relation to the NHPA. These were carried out as previously described [24]. Regarding the NHPA, polypropylene tubes with a volume of 10 mL were filled with 10 mg of MIP1 HPA /MIP1 PHE /MIP1 NBA / MIP1 NFE -MIP5 HPA /MIP5 PHE /MIP5 NBA /MIP5 NFE or NIP1-NIP5 particles.…”
Section: Binding Studiesmentioning
confidence: 99%
“…The binding mode of non-covalent molecular imprinting method and target components is generally weak covalent bond binding, such as hydrogen bond, van der Waals force, hydrophobic interaction, π-π accumulation (Yoshikawa et al, 2016;Vicario et al, 2018), etc. The recent literatures have reported that the interaction between the components of prepolymerization complex can be discussed by the theoretical analysis for design of functional monomers, cross-linking agents, and solvents (Sobiech et al, 2014(Sobiech et al, , 2017Cowen et al, 2016;Giebultowicz et al, 2019). Precipitation polymerization is the most commonly used method in the synthesis of imprint materials, but the main disadvantage of this method is that the steps required for the preparation of imprint materials are complex and numerous (Phungpanya et al, 2018).…”
Section: Introductionmentioning
confidence: 99%